Solder paste with high thermal conductivity and electrical conductivity and application thereof

By adding copper powder and specific flux to the solder paste, the conductivity and thermal conductivity of the solder paste is improved, and the problem of insufficient conductivity and thermal conductivity of the existing solder paste is solved, achieving more efficient soldering performance and longer service life .

CN119237986APending Publication Date: 2025-01-03NINGBO QIHAN NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411340899.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The lack of electrical and thermal conductivity of existing solder pastes limits their application in industrial production and experiments.

Method used

By adding a low proportion of copper powder to the solder paste and combining specific flux, active agent and solvent ratios, a high thermal conductivity solder paste is formed, including 10-20 parts of flux, 80-90 parts of metal powder, and copper The mass ratio of powder and tin powder is (20-3): 1. Specific solvents and active agents are used to remove oxides on the welding surface to improve welding performance.

Benefits of technology

It significantly improves the conductivity and thermal conductivity of solder paste, enhances welding performance, extends the service life of solder joints, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237986A_ABST
    Figure CN119237986A_ABST
Patent Text Reader

Abstract

The invention provides solder paste with high thermal conductivity and electrical conductivity, which comprises the following components in parts by mass: 10-20 parts of soldering flux and 80-90 parts of metal powder, the metal powder comprises copper powder and tin powder; the soldering flux comprises the following components in parts by mass: 3-8 parts of a thixotropic agent; 50-80 parts of an active agent and the balance of a solvent. The invention further provides application of the solder paste with high thermal conductivity and electrical conductivity in welding, which comprises the following steps: cutting a copper plate into a required size, cleaning, coating the copper plate with the solder paste with high thermal conductivity and electrical conductivity, selecting another copper plate to cover the solder paste to obtain a welding material, and putting the welding material into a welding machine for welding. Through the solder paste with high thermal conductivity and electrical conductivity, the problem that conventional solder paste is poor in electrical conductivity and thermal conductivity is solved, and the solder paste with high thermal conductivity and electrical conductivity is provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of solder paste preparation, and in particular to a solder paste with high thermal conductivity and electrical conductivity, and a preparation method and application thereof. Background Art

[0002] Tin paste is also called solder paste, a gray paste. Solder paste is a new type of welding material that came into being with SMT. It is a paste mixture formed by mixing solder powder, flux and other surfactants, thixotropic agents, etc. It is mainly used for welding electronic components such as resistors, capacitors, ICs, etc. on the surface of PCBs in the SMT industry; solder paste is a new type of welding material that came into being with SMT. Solder paste is a complex system, a paste mixed with solder powder, flux and other additives. Solder paste has a certain viscosity at room temperature, which can initially stick electronic components to a predetermined position. At the welding temperature, as the solvent and some additives evaporate, the components to be welded are welded to the printed circuit pads to form a permanent connection.

[0003] However, the tin in solder paste has a low melting point but insufficient thermal and electrical conductivity. The thermal conductivity of tin is only 1 / 6-1 / 7 of that of copper and silver, which also limits the application of solder paste. At present, the existing solder paste has poor electrical and thermal conductivity, which has a great impact on industrial production and experiments. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a solder paste with high thermal conductivity and electrical conductivity, so as to solve the problem of poor electrical conductivity and thermal conductivity of solder paste in the prior art.

[0005] In order to solve the above technical problems, the present invention provides a high thermal conductivity and electrical conductivity solder paste. Calculated by mass ratio, the high thermal conductivity and electrical conductivity solder paste includes: 10-20 parts of flux and 80-90 parts of metal powder; the metal powder includes copper powder and tin powder; the flux includes, by mass ratio: 3-8 parts of thixotropic agent; 50-80 parts of activator, and the balance is solvent.

[0006] Compared with the prior art, the high thermal conductivity and electrical conductivity solder paste in the present invention has the following advantages: in the formula of the above-mentioned high thermal conductivity and electrical conductivity solder paste in the present invention, in order to improve the thermal conductivity and electrical conductivity of the solder paste, a low proportion of copper powder is added to the solder paste. Since copper powder has excellent electrical conductivity, after mixing copper powder with other metals or alloys, a solder with high electrical conductivity and thermal conductivity can be obtained, and the thermal conductivity and electrical conductivity of the solder paste product are further improved by further compounding the proportion of raw materials.

[0007] In a possible embodiment, in the soldering flux, the solvent is selected from one or more of diethylene glycol dimethyl ether, propylene glycol methyl ether, diethylene glycol diethyl ether, tetrahydrofurfuryl alcohol, and ethanol; the thixotropic agent is selected from one or more of hydrogenated castor oil, ethylene bis(12-hydroxy)stearamide, polyamide wax, and fatty acid amide; the activator is selected from one or more of glutaric acid, DL-malic acid, succinic acid, methylsuccinic acid, suberic acid, sebacic acid, adipic acid, pimelic acid, azelaic acid, propylene glycol methyl ether acetate, and acetic acid.

[0008] Compared with the prior art, the above technical solution can better remove oxides on the surface of solder powder and copper particles, enhance the wettability between copper plate and metal powder, and improve its welding performance. The main function of the activator is to remove oxides and oil stains on the welding surface, making the welding surface cleaner, thereby improving the welding quality. It can remove oxidized substances on the surface of the pad and the welding position of the parts, and at the same time reduce the surface tension of tin and lead, which helps to improve the mechanical properties and corrosion resistance of the welded joint and extend the service life of the welded joint.

[0009] And by further selecting the solvent, the consistency and fluidity of the flux can be adjusted, making it easier to use. It has a regulating and balancing effect on the stirring process of the solder paste, and has a certain improvement in the service life of the solder paste.

[0010] The thixotropic agent further selected in the present invention can regulate the viscosity and printing performance of the flux, and has the effect of avoiding problems such as tailing and adhesion during printing, which helps to maintain the consistency of the solder paste in a static state and the fluidity during construction, ensuring the stability of the printing quality.

[0011] In a possible implementation, the method for preparing the soldering flux includes:

[0012] S1: Weigh the active agent, thixotropic agent and solvent according to the mass ratio;

[0013] S2: adding the solvent and the active agent of step S1 into a reaction container, setting the heating and stirring temperature to 100° C. until the active agent is dissolved to obtain a solution containing the active agent;

[0014] S3: Add the thixotropic agent of step S1 to the solution prepared in step S2, set the reaction temperature to 100-120° C., continue stirring until the thixotropic agent is completely dissolved, stir until the solution is in a paste state, stop stirring, and obtain solder flux.

[0015] Compared with the prior art, the homemade soldering flux prepared by the above-mentioned soldering flux preparation method of the present invention is halogen-free and highly active, can fully remove surface oxides of small-sized solder particles, can fully wet the soldering pad and the solder, and has good spreadability of the soldering point; and the homemade soldering flux has high activity to ultrafine tin-based solder powder.

[0016] In a possible implementation, in the step S2, the stirring speed is 400-600 rpm; in the step S3, the stirring speed is 900-1100 rpm.

[0017] In the above-mentioned embodiment, since the dissolution rate of the thixotropic agent in the preparation method of the present invention is relatively slow, the present invention increases the stirring speed in step S3 to accelerate the dissolution rate, and also improves the efficiency of the two stirrings.

[0018] In a possible implementation manner, the tin powder is SAC305, and the tin powder is spherical with a particle size of 5-20 microns.

[0019] In the above-mentioned embodiment, by selecting spherical solder powder, clogging of mesh holes is prevented, solderability is improved, defects are reduced, printing quality is further improved, and production costs are reduced;

[0020] In a possible implementation manner, the copper powder is spherical, and the copper powder is pure copper powder with a copper content greater than 99.5%, and the pure copper powder is spherical particles with a particle size of 5-8 and a diameter of 2-25 microns.

[0021] In a possible implementation manner, the mass ratio of the tin powder to the copper powder is (20-3):1.

[0022] In the above-mentioned embodiment, the ratio of tin powder to copper powder is controlled to achieve better welding effect and thermal conductivity;

[0023] Another technical problem to be solved by the present invention is to provide an application of the above-mentioned high thermal conductivity and electrical conductivity solder paste, wherein the application includes applying the high thermal conductivity and electrical conductivity solder paste to the welding of copper plates.

[0024] In one possible implementation, the application includes: cutting the copper plate to a desired size and then cleaning it, then coating the high thermal and electrical conductivity solder paste on the copper plate, selecting another copper plate to cover the solder paste to obtain a solder material, and then placing the solder material into a welding machine for welding.

[0025] The welding performed by the above possible implementation modes of the present invention has low welding test cost, can complete the welding test efficiently and quickly, and has good weldability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1This is a microscopic observation diagram of the welding cross section in the embodiment. DETAILED DESCRIPTION

[0027] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.

[0028] The invention provides a high thermal conductivity and electrical conductivity solder paste, which comprises, by weight ratio, 10-20 parts of soldering flux and 80-90 parts of metal powder; the metal powder comprises copper powder and tin powder; the soldering flux comprises, by weight ratio, 3-8 parts of thixotropic agent, 50-80 parts of activator, and the balance is solvent.

[0029] As a preferred embodiment, in the soldering flux, the solvent is selected from one or more of diethylene glycol dimethyl ether, propylene glycol methyl ether, diethylene glycol diethyl ether, tetrahydrofurfuryl alcohol, and ethanol; the thixotropic agent is selected from one or more of hydrogenated castor oil, ethylene bis(12-hydroxy)stearamide, polyamide wax, and fatty acid amide; and the activator is selected from one or more of glutaric acid, DL-malic acid, succinic acid, methylsuccinic acid, suberic acid, sebacic acid, adipic acid, pimelic acid, azelaic acid, propylene glycol methyl ether acetate, and acetic acid.

[0030] As a preferred solution, the preparation method of the soldering flux includes:

[0031] S1: Weigh the active agent, thixotropic agent and solvent according to the mass ratio;

[0032] S2: adding the solvent and the active agent of step S1 into a reaction container, setting the heating and stirring temperature to 100° C. until the active agent is dissolved to obtain a solution containing the active agent;

[0033] S3: Add the thixotropic agent of step S1 to the solution prepared in step S2, set the reaction temperature to 100-120° C., continue stirring until the thixotropic agent is completely dissolved, stir until the solution is in a paste state, stop stirring, and obtain solder flux.

[0034] As a preferred solution, in the step S2, the stirring speed is 400-600 rpm; in the step S3, the stirring speed is 900-1100 rpm.

[0035] As a preferred solution, the tin powder is SAC305, and the tin powder is spherical with a particle size of 5-20 microns.

[0036] As a preferred solution, the copper powder is spherical, and the copper powder is pure copper powder with a copper content greater than 99.5%, and the pure copper powder is spherical particles with a particle size of 5-8.

[0037] As a preferred solution, the mass ratio of the tin powder to the copper powder is (20-3):1.

[0038] The present invention also provides an application of the high thermal conductivity and electrical conductivity solder paste, which includes applying the high thermal conductivity and electrical conductivity solder paste to the welding of copper plates.

[0039] As a preferred solution, the application includes: cutting the copper plate to a desired size and then cleaning it, then coating the high thermal and electrical conductivity solder paste on the copper plate, selecting another copper plate to cover the solder paste to obtain a solder material, and then placing the solder material into a welding machine for welding.

[0040] The following provides specific embodiments combining actual data and data ranges to further illustrate and explain the technical scope of the above-mentioned scope of the present invention:

[0041] Embodiment 1:

[0042] Embodiment 1 provides a high thermal and electrical conductivity solder paste and a preparation method and application thereof, wherein the preparation method comprises:

[0043] Prepare the raw materials according to the following weight percentages:

[0044] 15 parts of solder paste and 85 parts of metal powder, wherein 15 parts of the solder paste is the self-developed solder paste of the present invention, the metal powder is 15% pure copper powder and 85% SAC305, the purity of the copper powder is>99.5%, and both the copper powder and SAC305 are No. 6 powder (particle size 10-20 microns).

[0045] Specifically, the flux contains 70% activator, 25% solvent and 5% thixotropic agent;

[0046] The active agent comprises 30% glutaric acid, 11% succinic acid, 10% acetic acid, 15% propylene glycol methyl ether acetate, and 34% DL-malic acid;

[0047] The solvent includes 30% diethylene glycol dimethyl ether and 70% propylene glycol methyl ether;

[0048] The thixotropic agent is ethylene bis stearamide;

[0049] The preparation method of the soldering flux comprises:

[0050] S1: Weigh the active agent and solvent according to the components;

[0051] S2: Pour the active agent into the solvent, set the heating temperature to 100°C, the stirring speed to 500 rpm, and stir until the active agent is completely dissolved;

[0052] S3: Pour the weighed ethylene bisstearamide into a beaker, set the heating temperature to 110°C and the rotation speed to 1000 rpm, and stir until the thixotropic agent is completely dissolved; store the prepared flux in a refrigerator.

[0053] The preparation method of the solder paste comprises:

[0054] Weigh 15g of flux, 12.75g of copper powder, and 72.25g of SAC305, stir the copper powder and SAC305 thoroughly and mix them evenly, then add the mixed metal powder to the flux paste, stir to make the flux and metal powder fully and evenly mix, stir for more than 10 minutes to form a solder paste, and store it at low temperature;

[0055] This embodiment also provides an application of the solder paste, specifically an application in copper plate welding. The actual welding process includes:

[0056] Cut the copper plate to the appropriate size, put it in an ultrasonic cleaner for cleaning for 3 minutes, take out the copper plate and soak it in a petri dish filled with alcohol, wipe it with hand towels when taking it out; take out the cleaned copper plate, put it on the balance to weigh it and record it, weigh the solder paste after setting it to zero, put it on the copper plate, take another copper plate of the same size to cover it and put it in the welding machine for welding, wait for the welding to be completed and take it out; observe the welding cross section under a metallographic microscope, such as Figure 1 As shown, from Figure 1 It can be seen that copper particles are evenly distributed in the middle solder layer.

[0057] The conductive solder paste prepared in Example 3 was tested and found to have a conductivity of 9.50*10 6 S / m (Siemens / meter), compared with the conventional solder paste without copper powder in the prior art and prepared by the same preparation method of the present invention, its conductivity is 7.7*10 6 S / m, the conductive solder paste prepared by the preparation method of the present invention has a significantly higher conductivity, and the conductive solder paste of the present invention is tested on the sample after welding in the embodiment after application, and its thermal conductivity reaches 105, compared with the conventional conductive solder paste, which generally has a thermal conductivity of about 50. The conductivity and thermal conductivity of the solder paste in this embodiment are greatly improved.

[0058] Embodiment 2:

[0059] Embodiment 2 provides a high thermal conductivity and electrical conductivity solder paste and a preparation method and application thereof. The high thermal conductivity and electrical conductivity solder paste comprises, by mass ratio:

[0060] 10 parts of flux and 80 parts of metal powder; the metal powder includes copper powder and tin powder; the flux is calculated by mass ratio and includes: 3 parts of thixotropic agent; 50 parts of activator, and the balance is solvent; the tin powder is SAC305, and the tin powder is spherical with a particle size of 5-10 microns; the copper powder is spherical, and the copper powder is pure copper powder with a copper content greater than 99.5%, and the pure copper powder is spherical particles with a particle size of No. 5; and the mass ratio of the tin powder to the copper powder is 3:1.

[0061] In the soldering flux, the solvent is a mixture of diethylene glycol dimethyl ether and propylene glycol methyl ether; the thixotropic agent is selected from a mixture of hydrogenated castor oil and ethylene bis(12-hydroxy)stearamide; and the activator is a mixture of glutaric acid, DL-malic acid, succinic acid, methylsuccinic acid, suberic acid, sebacic acid, adipic acid, and pimelic acid.

[0062] The preparation method of the soldering flux comprises:

[0063] S1: Weigh the active agent, thixotropic agent and solvent according to the mass ratio;

[0064] S2: adding the solvent and the active agent of step S1 into a reaction container, setting the heating and stirring temperature to 100° C. and the stirring speed to 400 rpm, until the active agent is dissolved to obtain a solution containing the active agent;

[0065] S3: Add the thixotropic agent of step S1 to the solution prepared in step S2, set the reaction temperature to 100° C., continue stirring until the thixotropic agent is completely dissolved, the stirring speed is 900 rpm, stir until the solution becomes a paste, stop stirring, and obtain flux.

[0066] This embodiment also provides an application of the high thermal conductivity and electrical conductivity solder paste, and the application includes applying the high thermal conductivity and electrical conductivity solder paste to the welding of copper plates.

[0067] The application includes: cutting the copper plate to a desired size and then cleaning it, then coating the high thermal and electrical conductivity solder paste on the copper plate, selecting another copper plate to cover the solder paste to obtain a solder material, and then putting the solder material into a welding machine for welding.

[0068] The conductive solder paste prepared in Example 3 was tested and found to have a conductivity of 9.40*10 6 S / m (Siemens / meter), compared with the conventional solder paste without copper powder in the prior art and prepared by the same preparation method of the present invention, its conductivity is 7.7*10 6S / m, the conductive solder paste prepared by the preparation method of the present invention has a significantly higher conductivity, and the conductive solder paste of the present invention is tested on the sample after welding in the embodiment after application, and its thermal conductivity reaches 98, compared with the conventional conductive solder paste, which generally has a thermal conductivity of about 50. The conductivity and thermal conductivity of the solder paste in this embodiment are greatly improved.

[0069] Embodiment 3:

[0070] Embodiment 3 provides a high thermal conductivity and electrical conductivity solder paste and a preparation method and application thereof. The high thermal conductivity and electrical conductivity solder paste comprises, by mass ratio:

[0071] 20 parts of soldering flux and 90 parts of metal powder; the metal powder includes copper powder and tin powder; the soldering flux is calculated by mass ratio and includes: 8 parts of thixotropic agent; 80 parts of activator, and the balance is solvent; the tin powder is SAC305, and the tin powder is spherical with a particle size of 15-20 microns; the copper powder is spherical, and the copper powder is pure copper powder with a copper content greater than 99.5%, and the pure copper powder is spherical particles with a particle size of No. 5; and the mass ratio of the tin powder to the copper powder is 20:1.

[0072] In the soldering flux, the solvent is a mixture of diethylene glycol dimethyl ether, propylene glycol methyl ether, diethylene glycol diethyl ether, tetrahydrofurfuryl alcohol, and ethanol; the thixotropic agent is a mixture of hydrogenated castor oil, ethylene bis(12-hydroxy)stearamide, polyamide wax, and fatty acid amide; and the activator is a mixture of glutaric acid, DL-malic acid, succinic acid, methylsuccinic acid, suberic acid, sebacic acid, adipic acid, pimelic acid, azelaic acid, propylene glycol methyl ether acetate, and acetic acid.

[0073] The preparation method of the soldering flux comprises:

[0074] S1: Weigh the active agent, thixotropic agent and solvent according to the mass ratio;

[0075] S2: adding the solvent and the active agent of step S1 into a reaction container, setting the heating and stirring temperature to 100° C. and the stirring speed to 600 rpm, until the active agent is dissolved to obtain a solution containing the active agent;

[0076] S3: Add the thixotropic agent of step S1 to the solution prepared in step S2, set the reaction temperature to 120° C., continue stirring until the thixotropic agent is completely dissolved, the stirring speed is 1100 rpm, stir until the solution becomes a paste, stop stirring, and obtain solder flux.

[0077] This embodiment also provides an application of the high thermal conductivity and electrical conductivity solder paste, and the application includes applying the high thermal conductivity and electrical conductivity solder paste to the welding of copper plates.

[0078] The application includes: cutting the copper plate to a desired size and then cleaning it, then coating the high thermal and electrical conductivity solder paste on the copper plate, selecting another copper plate to cover the solder paste to obtain a solder material, and then putting the solder material into a welding machine for welding.

[0079] The conductive solder paste prepared in Example 3 was tested and found to have a conductivity of 9.42*10 6 S / m (Siemens / meter), compared with the conventional solder paste without copper powder in the prior art and prepared by the same preparation method of the present invention, its conductivity is 7.7*10 6 S / m, the conductive solder paste prepared by the preparation method of the present invention has a significantly higher conductivity, and the conductive solder paste of the present invention is tested on the sample after welding in the embodiment after application, and its thermal conductivity reaches 100, compared with the conventional conductive solder paste, which generally has a thermal conductivity of about 50. The conductivity and thermal conductivity of the solder paste in this embodiment are greatly improved.

[0080] The above embodiments further prove that the present invention provides a high thermal conductivity and electrical conductivity solder paste and a preparation method and application thereof, and the solder paste prepared by the preparation method of the present invention improves the thermal conductivity and electrical conductivity of the solder paste. In the preparation method of the present invention, a low proportion of copper powder is added to the solder paste. Since the copper powder has excellent electrical conductivity, after the copper powder is mixed with other metals or alloys, a solder with high electrical conductivity and thermal conductivity can be obtained, which solves the problems existing in the prior art.

[0081] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0082] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A high thermal and electrical conductivity solder paste, characterized in that: Calculated by mass ratio, the high thermal and electrical conductivity solder paste includes: 10-20 parts of flux and 80-90 parts of metal powder; the metal powder includes copper powder and tin powder; the flux, calculated by mass ratio, includes: 3-8 parts of thixotropic agent; 50-80 parts of activator, and the balance is solvent.

2. The high thermal and electrical conductivity solder paste according to claim 1, characterized in that: In the soldering flux, the solvent is selected from one or more of diethylene glycol dimethyl ether, propylene glycol methyl ether, diethylene glycol diethyl ether, tetrahydrofurfuryl alcohol, and ethanol; the thixotropic agent is selected from one or more of hydrogenated castor oil, ethylene bis(12-hydroxy)stearamide, polyamide wax, and fatty acid amide; the activator is selected from one or more of glutaric acid, DL-malic acid, succinic acid, methylsuccinic acid, suberic acid, sebacic acid, adipic acid, pimelic acid, azelaic acid, propylene glycol methyl ether acetate, and acetic acid.

3. The high thermal and electrical conductivity solder paste according to claim 1, characterized in that: The preparation method of the soldering flux comprises: S1: Weigh the active agent, thixotropic agent and solvent according to the mass ratio; S2: adding the solvent and the active agent of step S1 into a reaction container, setting the heating and stirring temperature to 100° C. until the active agent is dissolved to obtain a solution containing the active agent; S3: Add the thixotropic agent of step S1 to the solution prepared in step S2, set the reaction temperature to 100-120° C., continue stirring until the thixotropic agent is completely dissolved, stir until the solution is in a paste state, stop stirring, and obtain solder flux.

4. The high thermal and electrical conductivity solder paste according to claim 3, characterized in that: In the step S2, the stirring speed is 400-600 rpm; in the step S3, the stirring speed is 900-1100 rpm.

5. The high thermal and electrical conductivity solder paste according to claim 1, characterized in that: The tin powder is SAC305, and the tin powder is spherical with a particle size of 5-20 microns.

6. The high thermal and electrical conductivity solder paste according to claim 1, characterized in that: The copper powder is spherical, and is pure copper powder with a copper content greater than 99.5%, and a particle size of the pure copper powder is 2-25 microns.

7. The high thermal and electrical conductivity solder paste according to claim 1, characterized in that: The mass ratio of the tin powder to the copper powder is (20-3):

1.

8. An application of the high thermal and electrical conductivity solder paste according to any one of claims 1 to 7, characterized in that: The application includes applying the high thermal and electrical conductivity solder paste to the welding of copper plates.

9. The use according to claim 8, characterized in that: The application includes: cutting the copper plate to a desired size and then cleaning it, then coating the high thermal and electrical conductivity solder paste on the copper plate, selecting another copper plate to cover the solder paste to obtain a solder material, and then putting the solder material into a welding machine for welding.